2005
DOI: 10.1016/s0002-9440(10)61246-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Nasal Sensitization Promote Distinct Immune Responses and Lung Reactivity in a Mouse Model of Peanut Allergy

Abstract: Despite structural and functional differences between the initial sites of contact with allergens in the gastrointestinal and nasal tracts, few animal models have examined the influence of the mucosal routes of sensitization on host reactivity to food or environmental antigens. We compared the oral and nasal routes of peanut sensitization for the development of a mouse model of allergy. Mice were sensitized by administration of peanut proteins in the presence of cholera toxin as adjuvant. Antibody and cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 79 publications
7
47
0
1
Order By: Relevance
“…We recently showed that mice challenged intranasally with peanut antigen developed eosinophil-mediated or neutrophil-mediated asthma depending of the initial nasal or oral route of sensitization [11]. Consistent with previous reports that both Th1 and Th2 cytokines are present in the lungs of asthmatic patients [12], Th1 and Th2 responses were not exclusive in orally sensitized (OS) and nasally sensitized (NS) mice.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…We recently showed that mice challenged intranasally with peanut antigen developed eosinophil-mediated or neutrophil-mediated asthma depending of the initial nasal or oral route of sensitization [11]. Consistent with previous reports that both Th1 and Th2 cytokines are present in the lungs of asthmatic patients [12], Th1 and Th2 responses were not exclusive in orally sensitized (OS) and nasally sensitized (NS) mice.…”
Section: Introductionsupporting
confidence: 84%
“…Plasma levels of peanut-specific Abs were measured by ELISA as previously reported [11]. To improve the detection of IgE Abs [21], IgG were removed from plasma samples by overnight incubation of samples at 4°C on protein G coated 96-well plates (Reacti-Bind plates, Pierce, Rockford, IL).…”
Section: Plasma Antibody Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of murine models of peanut-induced anaphylaxis (PIA) that mimic physiologic and immunologic features of human PA has facilitated both understanding of the underlying mechanisms and evaluation of potential therapeutic approaches (11)(12)(13). An important focus of these models has been on the role of Th2 responses in the regulation of sensitization (14 -16) and, subsequently, therapeutic strategies to redirect immune responses away from Th2 (17,18).…”
mentioning
confidence: 99%
“…For 17 consecutive days the T I-T III groups were treated with ethanol extract of D. alata correspond to with their doses, T IV group was treated with antihistamine drugs and T V group was treated with diosgenin. On day 15, the NC and T I -T V groups were induced with ovalbumin of 0,0483 mg/mice (Fischer et al, 2005modified by Diding et al, 2008. Mice were sacrificed on day 18, the lymphocytes were isolated from spleen and the absolute number of lymphocytes from pellet suspension of lymphocyte was counted with haemocytometer 3 times on minor chamber.…”
Section: Methodsmentioning
confidence: 99%